THE ASSOCIATION BETWEEN SCREEN TIME AND PSYCHOLOGICAL DISTRESS AMONG INDONESIAN FEMALE ADOLESCENTS: A CROSS-SECTIONAL STUDY - Alma Feriyanti; Rina Tri Agustini; Lies Permana; Nur Rohmah; Annisa Nurrachmawati; Agustin Putri Rahayu; Mohammad Fikri (Journal of Community Mental Health and Public Policy)
Background: Excessive smartphone use has a negative impact on health, especially in the adolescent age group. Adolescent females who screen time for two hours or more a day after school have the potential to experience psychological distress. Purpose: To analyze the relationship between screen time behavior and psychological distress in high school adolescent females. Methods: This quantitative study using a cross-sectional design. The research locations were carried out in three schools, namely SMA (Senior High School) 9 Balikpapan, SMA 2 Samboja and SMA 3 Penajam Paser Utara. The population was 1,112 adolescent females and the sample was 272 adolescent females.  The sampling technique used was proportional random sampling. The analysis test used the chi-square test. Variable measurements of screen time and psychological distress are used in the Questionnaire for Screen Time of Adolescents and the Kessler Psychological Distress Scale. Results: The p-value < 0.05 means that there is a relationship between screen time and psychological distress in high school adolescent females. Conclusion: Excessive screen time has an impact on the psychological distress of high school females. There is a need to increase mental health literacy and support for parents and schools in restricting the use of smartphones at home and at school.